From dynamic control to thermodynamic amplification: The structural redistribution of Iberian precipitation (1950–2024) - Eduardo A. Agosta; David Corell; Javier J. Miró; María José Estrela (Atmospheric Research, 2026)

Observed Changes in Maximum and Minimum Temperatures and Daily Temperature Range in the Iberian Peninsula and Balearic Islands Between 1952 and 2022 - David Corell; María José Estrela; Juan Javier Miró; David Orgambides‐García; Raquel Niclós (International Journal of Climatology, 2026)
Based on a dense series of temperature data from 3685 observatories located in peninsular Spain and on the Balearic Islands, the patterns and trends of the annual and seasonal values of the maximum, minimum and daily temperature range for the 1952–2022 period are analysed. To this end, this study analyses anomalies for the 1961–1990 period, trends in different time windows, spatial variations, and the influence of altitude and longitude on the three aforementioned variables. The main results are: (1) since the 1980s, positive anomalies of maxima and minima have been observed, with increasing values in recent decades; (2) summer and spring are the seasons with the highest maxima and minima anomalies, while a decrease in the diurnal temperature range values in autumn has been noted in recent decades; (3) since the 1970s, there has been a positive trend in maximum and minimum temperatures that, after a pause in the 2000s, regains strength given the high values recorded in recent years; (4) the trend in maximum temperature increases with altitude, with stations above 1500 m being the most affected. However, for minimum temperatures, urban stations below 250 m show the most marked trends; (5) the stations in the east are warming more quickly than those in the west. The high temperatures recorded in recent decades have led to a new upturn in temperature trends in the study area, which underlines the importance of regularly updating such studies. The influence of the increasingly warmer Mediterranean Sea may explain some of these changes.

Year-to-year fluctuations in fog-water collection in central Mediterranean Iberian Peninsula and the influential large-scale tropospheric circulation patterns - Eduardo Andres Agosta; David Corell; María José Estrela (Atmospheric Research, 2025)

Characterization of wildfire activity and relation to Fire Weather Index in the Valencia Region between 1993 and 2022 - David Orgambides-García; David Corell; María José Estrela; Juan Javier Miró; Raquel Niclòs (Theoretical and Applied Climatology, 2025)
Wildfire activity has decreased in the Valencia Region (Eastern Spain) in the last three decades in ignition and spread terms despite adverse climatological conditions caused by climate change, measured by the Fire Weather Index (FWI) in this study. We divided the study area into seven homogenous regions and split fires by cause to disaggregate the results, and to check for trends in these variables. The most relevant results were: 1) wildfire activity, especially in ignition terms, is decoupled from meteorological danger; 2) annual and interannual FWI variation fits changes in wildfire activity, although the decreasing fires trend masks any significant correlation; 3) summer is the most dangerous season, although large fires and adverse climatological conditions may occur in other seasons; 4) the majority of fires are manmade, with natural fires predominating in the northwest; 5) wildfires undergo significant regional differences that fit the type and intensity of the land use that predominates in each region; 6) the FWI is a good indicator of fire danger, and higher FWI values result in large and abundant fires; 7) responsible action and awareness have resulted in less wildfire activity in recent decades. While the increase in funds and equipment to prevent and combat fires has reduced their impact, ever more adverse conditions in the future caused by climate change will require making more effort to deal with wildfires by placing the focus beyond the warmest summer months.

Trend Analysis and Spatial Behaviour of the Fire Weather Index in the Mediterranean Iberian Peninsula, 1971–2022 - David Orgambides‐García; David Corell; María José Estrela; María Jesús Barberà; Javier Miró (International Journal of Climatology, 2024)
The Fire Weather Index (FWI) is a widely used metric to estimate the wildfire risk based on climatological variables. As anthropogenic climate change is expected to increase wildfire risk by affecting the climate of the Mediterranean Iberian Peninsula, we assess the expected increase in wildfire risk during the past decades. For this purpose, we employ a dataset containing daily FWI values in a 0.25° × 0.25° grid for each day of a 52‐year period, between 1971 and 2022, and perform a trend analysis at a statistically significant level. We evaluate the relation between FWI and spatial (altitude, latitude, and distance to the sea) variables to look for significant correlations. An analysis is performed at the geographic level by focusing on changes in concrete, relatively homogenous zones (subregions) to broadly study spatial patterns of change. The most relevant results are (1) the FWI shows an increasing trend across the study area (0.01 confidence level); (2) the FWI is determined by temperature variations on a multiyear scale, but annually by more volatile precipitation patterns; (3) the FWI does not uniformly behave across either space or time, and is subject to different variations in different zones; (4) summer and winter are the seasons with the most significant increase, and autumn is the only not significant season; (5) very high or extreme risks are increasingly prevalent across the territory, increasing wildfire risk and (6) the FWI more rapidly rises in areas further north, at a longer distance to the sea and at higher altitudes, with the Iberian System being the most affected region. The increase in wildfire risk requires putting in place more preventive measures. Our study results coincide with climatological trend studies on the region and bridge a knowledge gap as regards the historical climatology of the FWI.

Identification and quantification of flavor compounds in smoked tuna fish based on GC-Orbitrap volatolomics approach - Samia Mokh; Leticia Lacalle-Bergeron; David Izquierdo-Sandoval; M. Carmen Corell; Joaquim Beltran; Juan Vicente Sancho; Tania Portolés (Food Chemistry, 2024)

Assessment of water stress impact on olive trees using an accurate determination of the endocarp development - Marta Sánchez-Piñero; Mireia Corell; Laura L. de Sosa; Alfonso Moriana; Noemí Medina-Zurita; Engracia Madejón; Ignacio Girón; Pedro Castro-Valdecantos; María José Martín-Palomo; David Pérez-López (Irrigation Science, 2024)
When considering deficit irrigation, the most resistant period to water stress in olive crops is during the pit hardening. However, the determination of this period and the impact that water stress has on its onset or duration have not been clearly established. The aim of this work is to describe the impact of water stress on three processes that determine fruit development: fruit growth, endocarp hardening, and oil accumulation. This experiment was conducted between 2021 and 2022, in a plot with olive trees that were 3 years old at the beginning of the experiment. The young trees were of cv Manzanilla de Sevilla and were planted in a 4 × 1.5 m frame. The treatments were: Control, irrigated close to what is considered the optimum level in which the water status of the crop ensures the absence of water stress; RDI, with a moderate stress during the pit hardening stage; Rainfed and Traditional Rainfed. This latter was included only in 2022 using a 7 × 5 m frame. Traditional Rainfed was included to compare with Rainfed, these were similar in the maximum level of water stress but not in the duration. The fruit growth, oil accumulation, and endocarp hardness were measured for a period of 2 years. The hardness curves fit accurately established Period II which was the one with the fast hardness increases. The water potential was measured periodically on leaves at midday, whereby the minimum and average potential and the stress integral were obtained for each of the periods indicated before using pit hardness measurements. The results suggest that endocarp hardening was the process most resistant to water stress, as it showed very little variation from the seasonal pattern, despite the high levels of stress achieved. The fruit growth process was the most sensitive to water stress, but the recovery was fast in conditions of moderate water stress level. The oil accumulation started slowly during Period II, but its rate increased at the end of the period. This later process was moderately resistant to water stress. However, although the accumulation rate was faster during Period III, it was influenced by the water status during Period II. Cumulative water stress was related with fruit growth and oil accumulation processes. Endocarp development could be useful for determining a/the deficit irrigation period because of its almost constant pattern. These periods would permit water management optimization according to final use of the fruit (oil or table). However, continuous monitoring of water stress would be needed.

Precipitation and drought trends (1952–2021) in a key hydrological recharge area of the eastern Iberian Peninsula - Juan Javier Miró; María José Estrela; David Corell; Igor Gómez; María Yolanda Luna (Atmospheric Research, 2023)

Seasonal behaviour and influence of altitude on fog‐water collection in the Eastern Iberian Peninsula (2003–2012) - David Corell; María José Estrela; José Antonio Valiente (International Journal of Climatology, 2023)
A study on fog‐water collection potential at the Mediterranean Iberian Peninsula was carried out for the period 2003–2012. The area is denoted by a high population density, with fairly common water restrictions in certain periods during the year. Moreover, climate change projections point out a sharp drop in precipitation for this sector of the western Mediterranean Basin that would aggravate water problems. This work aims to look closely at knowledge of fog‐water collection and it presents results about: its behaviour during different seasons of the year; the fog‐water collection potential on dry days (precipitation −2 at more than half the studied sites; (c) the greater the positive difference in elevation between nearby stations, the larger the positive difference in both fog collected volumes and fog days at equal exposition to prevailing winds, differences that increase in the summer period. Mount Muela (Murcia Region), combining a pair of stations only distanced by 600 m but at a 92‐m elevation difference, reported a contrast of two times the collected volume at the upper station compared to the lower and an increment of 61% more days with fog occurrence. Mount Montseny (Catalonia), with a pair of stations distanced by 1,600 m horizontally and 398 m in elevation difference, obtained a sixfold variation between stations for fog‐water collection and a 73% increment in foggy days.

Influences of synoptic situation and teleconnections on fog‐water collection in the Mediterranean Iberian Peninsula, 2003–2012 - David Corell; Maria J. Estrela; Jose A. Valiente; Cesar Azorin‐Molina; Deliang Chen (International Journal of Climatology, 2020)
Fog‐water collection has been widely analysed for its quantification and potential uses; however, there are few studies assessing the synoptic conditions and large‐scale teleconnection patterns that affect its occurrence. Focusing on the Mediterranean Iberian Peninsula, this work aims to analyse the synoptic patterns, both at surface level and 850 hPa geopotential height, that most likely to favour fog‐water collection, and to quantify the relationship between fog‐water collection and the NAOi (North Atlantic Oscillation index), MOi (Mediterranean Oscillation index) as well as WeMOi (Western Mediterranean Oscillation index) teleconnection patterns. For this purpose, daily fog‐water observations from a dense network of 23 fog‐water collectors located along the Mediterranean Iberian Peninsula for 2003–2012 were analysed in relation to synoptic patterns and the three‐teleconnection indices. The major findings are: (a) The most favourable synoptic patterns for fog‐water collection are maritime advections carrying humidity from the Mediterranean basin, and cyclonic circulations, whereas anti‐cyclonic situations generally led to large number of foggy days with low fog‐collection rates. (b) In terms of winds at 850 hPa, the most favourable low‐level flows for fog‐water collection are associated with strong winds (>5.1 m s −1 ) from the Mediterranean. Atlantic winds generally cause a greater number of fog days than Mediterranean winds, with less fog‐water collection rates. (c) WeMOi has the greatest influence on fog‐water collection, mainly during winter and spring months, with statistically significant negative relationships for most of the stations. MOi also shows a great influence, with a large number of statistically significant negative correlations, mainly during the same months as WeMOi. Lastly, NAOi presented the lowest and no significant negative correlations with fog‐water collection.

Climate controls on rainfall isotopes and their effects on cave drip water and speleothem growth: the case of Molinos cave (Teruel, NE Spain) - Ana Moreno; Carlos Sancho; Miguel Bartolomé; Belén Oliva-Urcia; Antonio Delgado-Huertas; Mª José Estrela; David Corell; Juan Ignacio López-Moreno; Isabel Cacho (Climate Dynamics, 2014)

Fog as a Fresh-Water Resource: Overview and Perspectives - Otto Klemm; Robert S. Schemenauer; Anne Lummerich; Pilar Cereceda; Victoria Marzol; David Corell; Johan van Heerden; Dirk Reinhard; Tseggai Gherezghiher; Jana Olivier; Pablo Osses; Jamal Sarsour; et al. (Ambio, 2012)

Understanding Climatic Impacts, Vulnerabilities, and Adaptation in the United States: Building a Capacity for Assessment - Edward A. Parson; Robert W. Corell; Eric J. Barron; Virginia Burkett; Anthony Janetos; Linda Joyce; Thomas R. Karl; Michael C. MacCracken; Jerry Melillo; M. Granger Morgan; David S. Schimel; Thomas Wilbanks (Climatic Change, 2003)